Morphological device model for organic bulk heterojunction solar cells - Maturová, Klára; Bavel, Svetlana S. van; Wienk, Martinus Maria; Janssen, René A. J.; Kemerink, Martijn (Nano letters, 2009)
We present a numerical model for calculating current-voltage characteristics of polymer:fullerene bulk hetrojunction solar cells at different degrees of nanoscale phase separation. We show that the short-circuit current enhancement with finer phase separation is due to a reduction in bimolecular recombination caused by lateral movement of photogenerated electrons to the fullerene-rich phase. At high bias, vertical electron transport is enhanced and lateral movement is reduced, causing a significant field-dependent carrier extraction for coarse morphologies.
Gesehen am 16.12.2019